2012
DOI: 10.1037/a0023959
|View full text |Cite
|
Sign up to set email alerts
|

Eye gaze versus arrows as spatial cues: Two qualitatively different modes of attentional selection.

Abstract: This study aimed to evaluate the type of attentional selection (location- and/or object-based) triggered by two different types of central noninformative cues: eye gaze and arrows. Two rectangular objects were presented in the visual field, and subjects' attention was directed to the end of a rectangle via the observation of noninformative directional arrows or eye gaze. Similar experiments with peripheral cues have shown an object-based effect: faster target identification when the target is presented on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
106
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 45 publications
11
106
1
Order By: Relevance
“…Taken together, the results of Experiments 1, 2 and 3 suggest that a spatial cueing mechanism may be engaged in the dot perspective task if an SOA is involved, but that this is unlikely to explain the findings from standard versions of the paradigm that do not include an SOA. This is consistent with the findings of Marotta, Lupiánez, Martella, & Casagrande (2012), who systematically varied not only the locations of targets, but also the objects (i.e. rectangular figures) in which those targets appeared, and were thereby able to show that faces, unlike arrows, trigger a pure location-based cueing effect, whereas arrows, unlike faces, trigger a pure object-based cueing effect.…”
Section: Discussionsupporting
confidence: 88%
“…Taken together, the results of Experiments 1, 2 and 3 suggest that a spatial cueing mechanism may be engaged in the dot perspective task if an SOA is involved, but that this is unlikely to explain the findings from standard versions of the paradigm that do not include an SOA. This is consistent with the findings of Marotta, Lupiánez, Martella, & Casagrande (2012), who systematically varied not only the locations of targets, but also the objects (i.e. rectangular figures) in which those targets appeared, and were thereby able to show that faces, unlike arrows, trigger a pure location-based cueing effect, whereas arrows, unlike faces, trigger a pure object-based cueing effect.…”
Section: Discussionsupporting
confidence: 88%
“…As a consequence, gaze cues directed toward occluded objects are often interpreted as not conveying social meaning, with the observer ceasing to experience typical gaze‐induced object preferences . This behavior may be explained by the attribution of an intention to attend to specific objects, as, for example, nonsocial arrow cues have been shown to elicit a general location bias toward parts of the environment, while gaze cues have been shown to elicit spatial‐orienting effects toward a specific object location . Consistent with this hypothesis, Perez‐Osorio and colleagues reported that gaze‐following behaviors became reduced when gaze direction violated context‐driven expectations regarding an agent's action toward available objects …”
Section: The Three Core Processesmentioning
confidence: 95%
“…Relevantly, research by Marotta et al (2012) have also shown different forms of attentional selection between eye-gaze and arrows even with a gaze-cueing paradigm. Authors displayed two rectangles, in which one end or another of one of them was cued by a central non-informative directional eye-gaze or arrow cue, and then succeeded by a target presented in one end of those rectangles.…”
Section: Introductionmentioning
confidence: 93%
“…However, it is important to note that the study of Marotta et al (2012) was the first that ever assessed the type of attentional selection elicited by eye-gaze and arrow cues and that most of the participants of the study were female. For this reason, assuming the natural variations in the effect triggered by gaze cues across individuals, the interpretation of the findings observed in their study must be cautious and should not be necessarily extended to the general population.…”
Section: Introductionmentioning
confidence: 99%